What management is versus what managers do: An investigation into required management course offerings for undergraduate business students. Issue 2 (July 2022) - Fertig, Jason; Joseph, Meg L.
Abstract: Many schools do not require business students to take a Principles of Management course, even though the four management principles of planning, organizing, leading and controlling purport to anchor the discipline and are the framework for popular Principles texts. Based on guidance from other curricular research (Aasheim, Williams, Rutner, & Gardiner, 2015; Kung, Yang, & Zhang, 2006; Mishra, Day, Littles, & Vandewalker, 2011), this study investigated the management courses required of all business majors at 114 AACSB-accredited schools in the United States. Results showed that less than half required Principles of Management, with many choosing instead to require a course focused on people management (e.g., Organizational Behavior). Disagreement over the core aims of the required management course for all business majors leaves gaps in their education. Given our findings, we suggest goals for organizing a management course to reflect the full spectrum of what the job of manager entails. Highlights: Less than half of surveyed schools required Principles of Management as the required management course for business majors. Many business schools are adopting courses more focused on individual and group behavior as their core management course. Disagreement over the core aims of the required management course for all business majors leaves gaps in students' education. The ideal management course reflects the full spectrum of the manager's job – managing people and managing work.